Kedudukan UU Cipta Kerja Terhadap UU-PPLH dan Implikasinya - Helmi - Helmi (Fakultas Hukum Universitas Riau, 2021)
Law of job creation (UU-CK) already change, remove, and shift the new norm of law of environmental protection (UU-PPLH) in today potentially to create a matter and second legal conflict for this law in the action and law enforcement in the future. Among the urgency of economic affair through the acceleration of investment will face off the urgency of the protection and environmental management. Both matters come as the focus on this article analysis here are these, first the legislation as a system and implication of job creation's law legality against UU-PPLH as environmental clustering in Indonesia. Second, the implication of the change of UU-PPLH due to UU-CK. Here is the conclusion, first the change of UU-PPLH's primary norm due to UU-CK will impact on another norm which the legality directly related on the protection and environmental management overall. Second, the implication identified from the content material, both law potentially to create a norm conflict on the action and law enforcement. Meanwhile, if this case related to the principle of legal conflict settlement, then no principle can be used either the principle of lex specialis derogat legi generalis, the principles of Lex superior derogat legi inferior, and the principles of lex posterior derogat legi priori. To encounter the norm conflict matter, the better one in reformating regulation in the way of Omnibus law method, despite it is limited on the system of clustering and organization, but also not repeal and state the illegality of the impacted regulation.